90.1k views
4 votes
(4+6i)(7-5i)

Simplify :

2 Answers

1 vote

Answer:

58 + 22i

Explanation:

We know:


√(-1)=i\to i^2=-1


(4+6i)(7-5i) use FOIL: (a + b)(c + d) = ac + ad + bc + bd


=(4)(7)+(4)(-5i)+(6i)(7)+(6i)(-5i)\\\\=28-20i+42i-30i^2\\\\=28-20i+42i-30(-1)


=28-20i+42i+30 combine like terms


=(28+30)+(-20i+42i)\\\\=58+22i

User Aditya Sanghi
by
5.3k points
2 votes

Answer:

(4+6i)(7-5i) = 58 + 22i

Explanation:

Given that:

=(4+6i)(7-5i)

We can write it as follows:

=4(7-5i)+6i(7-5i)

=28-20i + 42i - 30i^2

As i^2 = -1 So:

= 28 + 22i - 30(-1)

= 28 +22i +30

= 58 + 22i

I hope it will help you!

User Ggeop
by
5.2k points